Manajemen pengembangan profesionalisme guru dalam rangka implementasi kurikulum 2013 di SMA Negeri 1 Wonosari Gunungkidul Yogyakarta tahun pelajaran 2014/2015 - Siti Zumrotul Arifah; Supriyoko Supriyoko (Wiyata Dharma: Jurnal Penelitian dan Evaluasi Pendidikan, 2016)
The goal of this research is to describe the management of professional development of teacher’s in implementing the curriculum 2013, by expressing (1) the strategy undertaken in the framework in implementing the curriculum, (2) management the implementation of professional development of teachers implementing the curriculum 2013, (3) inhibiting factors in the implementation of professional development of teacher‘s in the implementation of curriculum 2013 in the state senior  high school 1 of Wonosari. The research method used was a qualitative method. Data collection was done by interviews, documentation and observation. The process of data analysis began by examining all of the data available from various sources, from interviews, observations that have been written in the field notes, personal documents and official documents. The results showed that: (1) strategies implemented in the framework in implementing the curriculum 2013 carried through the stages of planning, organizing, implementation,  monitoring, and evaluation that goes with good and satisfactory (2) Implementation of teacher professional development program realized in the form of activities that include: training, implementation and preparation of classroom action research (CAR), implementing lesson study and implementation of workshop curriculum 2013 The factors that hinder the implementation of teacher professional development programs in implementing the curriculum 2013, among others: (a) Internal factors including: the ability and commitment of teachers in the completion of the task, (b) external factors, including: training events which are materially less ready (c) the workload of 24 hours (d) the difficulty of determining the exact time of program development. Steps taken by the principal in overcoming these obstacles include: (a) holding the selection of participants training Dikpora organized by Province and Ministry of National Education (b) Optimizing dissemination after activities of workshops outside of school, (c) conducting the program at the time of semester holidays or after the learning process is completed, and (d) to cooperating with relevant competent agencies DIY Province namely LPMP  (e) intensifying the activities of MGMP.